Wave energy resource in the North Sea - Beels, C. (2009)
Due to the high potential of wave energy and the goal to raise the share of renewable energy supply in the EU up till 20 % in 2020, the development of wave energy is accelerated. Until now the wave energy resource was highlighted in regions with a high wave energy density. As Wave Energy Converters (WECs) still contend with problems such as structural strength and mooring in a severe and energetic wave climate, the prospects of wave power conversion in a less aggressive wave climate should be investigated. This paper describes the wave power resource in a rather sheltered area i.e., the North Sea. The available wave power is studied on 34 locations. Characteristic sea states are defined for the Belgian, Dutch, German, Danish, Norwegian and UK Continental Shelf. An inverse-ray refraction model, implemented at INETI (Instituto Nacional de Engenharia, Tecnologia e Inovação), is presented to calculate the resource on more convenient locations for wave energy conversion. The wave power potential in the North Sea is compared with the resource of the West European coast. Near shore (< 30 km off the coast) up to a maximum of approximately 11 kW/m is available in the North Sea.